GERMINATION OF TOMATO SEEDS (Solanum Lycopersicum L.) BASED ON SEED AGE AND TYPE OF SEEDLING MEDIA USING THE F&F MANUAL GERMINATOR TOOL: PERKECAMBAHAN BENIH TOMAT (Solanum Lycopersicum L.) PADA UMUR BENIH DAN JENIS MEDIA SEMAI MENGGUNAKAN ALAT F&F MANUAL GERMINATOR - Faisal; Ismady; Muhammad Rafli; Muhammad Yusuf Nurdin; Anwar Puteh (ROCE : Jurnal Pertanian Terapan, 2026)
The purpose of this study was to determine the effect of different seed age treatments and seedling media types on seed viability and vigor of tomato seeds. The results showed that seed age treatments significantly affected germination rate, vigor index, growth synchrony, growth rate, normal seedling length, and normal seedling fresh weight. Meanwhile, different seedling media treatments significantly affected tomato seed viability and vigor. Furthermore, there was a significant interaction between seed age treatments and media types on all parameters of tomato seed viability and vigor.